A SISTEM KEAMANAN ROMBONG MENGGUNAKAN SENSOR PIR DAN SENSOR SW-420 DENGAN OUTPUT MODUL GSM SIM800L V2 DI TERMINAL SUMER PAYUNG - Hidayatullah, Muhammad; Dimas Utomo; Ahmad Jaya; Topan, Paris Ali (Jurnal Altron, 2024)
The security system is a key factor in protecting a person's property from criminal acts, for example theft, the use of the security system for the Sumer Payung Terminal UMKM rombong is one of the implementations of a security system to protect the goods sold and property in the rombong, using a PIR sensor which functions to detecting movement in front of the house, the SW-420 sensor or vibration sensor functions to detect vibrations in the house, and the GSM SIM800L V2 module functions to send an SMS to the house owner that an act of theft has occurred. at the testing stage of this security system, the results were in accordance with what was planned, including the results of testing the PIR sensor 5 times, getting results at a distance of 3cm - 1 m, the PIR sensor could detect movement, while at a distance of 1.5 m - 2 m, the PIR sensor could not. can detect movement, the SW-420 sensor in this test took 3 vibration samples, namely vibration using hands, vibration using wood, and vibration using iron. The results were that the SW-420 sensor could detect vibrations from these 3 samples. The results of the rombong security system test works as desired